Two new species of the genus Macromotettix Günther, 1939 (Orthoptera: Tetrigidae, Metrodorinae) from China, with a key to the species of the genus - Deng, Wei-An; Xin, Lei; Wei, Qiao; Chen, Ya-Zhen (Zootaxa, 2018)
Taxonomy of a tetrigid genus Macromotettix Günther is reviewed. Two new species, Macromotettix undulatifemura Deng sp. nov. and Macromotettix sichuanensis Deng sp. nov. are described from China. An updated identification key to all known species of the genus are given.